Fragile beasts : a novel - O'Dell, Tawni (New York : Broadway Paperbacks, 2010)
Two teenagers have grown up raggedy in Pennsylvania coal country with their alcoholic father, whose death prompts the return of their truly awful mom.
Keywords: Teenage boys -- Fiction; Older women -- Fiction; Coal miners -- Fiction; City and town life -- Pennsylvania -- Fiction; Pennsylvania -- Fiction